MENIMBUN BAHAN BAKAR MINYAK (BBM) DALAM PERSPEKTIF HUKUM ISLAM (Mazahib, 2013)
There are two categories of hoarding fuel. One of them is ihtikaar and the other one is not ihtikaar. The hoarder of fuel that is included ihtikaar deserves punishment with certain conditions. The punishment is ta’ziir. While the executant that is not included ihtikaar has no problem. The hoarded fuel is seized by the state. However, the state does not deserve to possess it totally and automatically. The state is arbitrary and inequitable if it possesses the seized fuel totally.